Sereniss. Principi Philippo Wilhelmo Com. Palat. Rheni, Bavar. Iul. Cliu. Mont. Duci, Veldentij, Sponhemij, Marchiæ, Ravenspurgi, Mœrsij Comiti, Domino in Ravensteijn, etc. - Aubry, Peter (1653)
Bildoval, Bruststück